Adenosine mediates functional and metabolic suppression of peripheral and tumor-infiltrating CD8+ T cells. Issue 1 (10th October 2019) - Mastelic-Gavillet, Beatris; Navarro Rodrigo, Blanca; Décombaz, Laure; Wang, Haiping; Ercolano, Giuseppe; Ahmed, Rita; Lozano, Leyder Elena; Ianaro, Angela; Derré, Laurent; Valerio, Massimo; Tawadros, Thomas; Jichlinski, Patrice; et al.
Abstract : Background: Several mechanisms are present in the tumor microenvironment (TME) to impair cytotoxic T cell responses potentially able to control tumor growth. Among these, the accumulation of adenosine (Ado) contributes to tumor progression and represents a promising immunotherapeutic target. Ado has been shown to impair T cell effector function, but the role and mechanisms employed by Ado/Ado receptors (AdoRs) in modulating human peripheral and tumor-infiltrating lymphocyte (TIL) function are still puzzling. Methods: CD8 + T cell cytokine production following stimulation was quantified by intracellular staining and flow cytometry. The cytotoxic capacity of tumor infiltrating lymphocytes (TILs) was quantified by the chromium release assay following co-culture with autologous or anti-CD3-loaded tumor cell lines. The CD8 + T cell metabolic fitness was evaluated by the seahorse assay and by the quantification of 2-NBDG uptake and CD71/CD98 upregulation upon stimulation. The expression of AdoRs was assessed by RNA flow cytometry, a recently developed technology that we validated by semiquantitative RT-PCR (qRT-PCR), while the impact on T cell function was evaluated by the use of selective antagonists and agonists. The influence of Ado/AdoR on the PKA and mTOR pathways was evaluated by phosphoflow staining of p-CREB and p-S6, respectively, and validated by western blot. Results: Here, we demonstrate that Ado signaling through the A2A receptor (A2AR) in human peripheral CD8 + T cells and TILs is responsible for the higher sensitivity to Ado-mediated suppression of T central memory cells. We confirmed that Ado is able to impair peripheral and tumor-expanded T cell effector functions, and we show for the first time its impact on metabolic fitness. The Ado-mediated immunosuppressive effects are mediated by increased PKA activation that results in impairment of the mTORC1 pathway. Conclusions: Our findings unveil A2AR/PKA/mTORC1 as the main Ado signaling pathway impairing the immune competence of peripheral T cells and TILs. Thus, p-CREB and p-S6 may represent useful pharmacodynamic and efficacy biomarkers of immunotherapies targeting Ado. The effect of Ado on T cell metabolic fitness reinforces the importance of the adenosinergic pathway as a target for next-generation immunotherapy.